(untitled) (The Lumbini Journal of Business and Economics, 2023)
The Volume XI, No.2 issue of “The Lumbini Journal of Business and Economics”, is ready now for catering the need of this time from Lumbini Banijya Campus. I would like to take this privilege today to share with you that the Research and Development Department of Lumbini Banijya Campus is rigorously dedicating for the enhancement of quality research in this region. The small step from LBC would ultimately add value to all the researchers to conduct their research works. We the entire editorial team expresses sincere gratitude to the respective contributors who not only contributed their invaluable research paper but also provides critical appreciative comments to bring the journal lively. The team also expresses sincere thanks to president, Campus Management Committie of LBC Mr. Motilal Pandey, Campus Chief Prof. Dr. Tara Prasad Upadhaya, all reviewers, all the falculties, staffs and students of LBC for the supportive attitude to bring this issue into final form. The Vol. XI, No.2 issue contains altogether eight research papers of diffrent flavour to cater the needs of current business and economic environment of Nepal as well as International arena. We the editorial team left no stone unturned to make this issue completely free from errors but you know that “TO ERROR IS HUMAN” so if you point out and suggest us then that would be our positive direction for the future. I offer sincere thanks to all my team members of editorial board for their great support to bring the issue in the hand of readers. Editor-in-Chief December, 2023